Examining gender empowerment during Unilever's CSR activities: social communication aspects - Nova Dwiyanti; Hasan Sazali; Anang Anas Azhar (Faculty of Communications Science, Dr. Soetomo University, 2024)
This study investigates how gender empowerment affects Unilever's CSR social media output. Given the increasing relevance of CSR in corporate identity and social development, this research examines how well CSR initiatives could convey and support female emancipation. With an eye towards Unilever, a global business leader, the company emphasises sustainability and responsibility. This paper argues that corporate strategy depends on CSR and that social justice and sustainable development depend on women's empowerment. The study looks at the junction of gender and corporate responsibility using feminist theory and corporate communication, therefore investigating how CSR social media may empower women. Additionally , Unilever's CSR and gender empowerment reports as well as community leaders were examined and interviewed. This method makes clear the objectives of female empowerment and CSR. Initial results imply that CSR projects by Unilever help women. Good social communication plans call for respect of indigenous cultural norms and values, open communication, and community involvement. Emphasising the need of integrating women in the design and execution of CSR projects to meet their needs and viewpoints. The studies stress that there are important pragmatic implications from this research. It presents a disciplined framework to assess the social justice impact of corporate actions and offers strategic social communication recommendations for empowering women via CSR, hence, improving CSR and gender research. The report highlights opportunities for development in CSR strategies and best practices, therefore guiding governments and corporate leaders. According to the results, women can be empowered by CSR; social influence depends mostly on communication. Thus, a more complete CSR plan and communication must prioritise social justice—especially women's empowerment.